Restoration of Bilateral Cranial Defects by Hybridization of Microvascular Free Flaps and Artificial Bones. Issue 9 (September 2019) - Mashiko, Takanobu; Minabe, Toshiharu; Ohnishi, Fumio; Momosawa, Akira
Abstract : Summary: Although treatment methods for cranial reconstruction have significantly improved over the past decades, patients having potentially negative influences, such as a history of infection, epidural dead space, or inadequate scalp, remain at high risk of postoperative failure from implant infection and exposure necessitating removal. A 41-year-old male patient sustained severe craniofacial injuries in a traffic accident. Cranioplasty with titanium mesh implants failed due to implant infection, leading to implant removal and debridement. Following repeated local infections and a craniectomy, the patient developed large bilateral complex cranial defects. We then performed a multistage operation, consisting of vascularized free-flap transfers to cover the intracranial dead spaces, and bony reconstruction using hydroxyapatite implants, which achieved full restoration of the defects. We believe that this is the better operative plan for treatment of cranial defects in patients with high-risk factors.